Reconstructing the retreat dynamics of the Bjørnøyrenna Ice Stream based on new 3D seismic data from the central Barents Sea - Piasecka, Emilia Daria; Winsborrow, Monica; Andreassen, Karin; Stokes, Chris R. (Quaternary Science Reviews, 2016)
Accepted manuscript version. Published version available in Quaternary Science Reviews (2016) 151, p. 212-227. The stability of contemporary ice sheets is influenced by the discharge from ice streams - corridors of fast-flowing ice bounded by ice flowing an order of magnitude slower. Reconstructions of palaeo-ice stream dynamics contribute to our understanding of ice stream sensitivity to the ocean-climate system and can aid in the numerical modelling and prediction of future changes in contemporary ice sheets. Here we use 3D seismic data, covering 13,000 km2 in the central Bjørnøyrenna (Bear Island Trough), Barents Sea, to investigate the record of ice streaming preserved on the seafloor and on a buried palaeo-seafloor surface. The unusually broad coverage and high resolution of the dataset, as well as its location in the central area of the trough, enables improved reconstruction of dynamics of the former Bjørnøyrenna Ice Stream in terms of number of streaming events, their trajectory, and their relative age sequence during deglaciation. Our results reveal major changes in the configuration and flow dynamics of the ice stream, with up to 10 flow-switching events identified. For the first time, we also document ice streaming sourced from the eastern Barents Sea around the time of the LGM. This high degree of flow variability is suggested to have resulted from climate-driven changes in ice sheet geometry (and ice divide migration), and variations in topography that influenced calving at the ice stream terminus.